Sub-poissonian statistics of rydberg-interacting dark-state polaritons - Hofmann, Christoph S.; Günter, Georg; Schempp, Hanna; Robert-de-Saint-Vincent, Martin; Gärttner, M.; Evers, J.; Whitlock, Shannon; Weidemüller, Matthias (Physical review letters, 2013)
We observe individual dark-state polaritons as they propagate through an ultracold atomic gas involving Rydberg states coupled via an electromagnetically induced transparency resonance. Strong long-range interactions between Rydberg excitations give rise to a blockade between polaritons, resulting in large optical nonlinearities and modified polariton number statistics. By combining optical imaging and high-fidelity detection of the Rydberg polaritons we investigate both aspects of this coupled atom-light system. We map out the full nonlinear optical response as a function of atomic density and follow the temporal evolution of polaritons through the atomic cloud. In the blockade regime, the statistical fluctuations of the polariton number drop well below the quantum noise limit. The low level of fluctuations indicates that photon correlations modified by the strong interactions have a significant backaction on the Rydberg atom statistics.